Tuberculosis in Nepal: Diagnosis and Treatment Barriers - Marahatta, SB; Karki, BJ (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.1-2